Impact of foreign direct investment on economic growth: Peruvian analysis from the years 1980 to 2020 - Campana Salgado, Lessly Paola (2021)
The objective of this research was to identify the impact of the foreign direct investment variable on the economic growth variable in Peru, period 1980-2020. The methodology developed had a quantitative orientation, whose design was non-experimental of longitudinal cut, considering an evaluation of the data in a prolonged period of years. The technique applied was documentary analysis and review. The data obtained from the BCRP was used, which identified the impact and influence of foreign investment on economic growth, measured in terms of GDP through a VAR model with the two variables and the development of the Johansen Cointegration test. Finally, based on the results obtained, it is concluded that there is evidence of a positive direct relationship between the foreign direct investment variable and the economic growth variable from 1980 to 2020, since there is at least one vector or cointegration relationship in the long term.